Exploring microbial determinants of apple replant disease (ARD): a microhabitat approach under split-root design. Issue 12 (12th October 2020) - Balbín-Suárez, Alicia; Lucas, Maik; Vetterlein, Doris; Sørensen, Søren J; Winkelmann, Traud; Smalla, Kornelia; Jacquiod, Samuel
ABSTRACT: Apple replant disease (ARD) occurs worldwide in apple orchards and nurseries and leads to a severe growth and productivity decline. Despite research on the topic, its causality remains unclear. In a split-root experiment, we grew ARD-susceptible 'M26' apple rootstocks in different substrate combinations (+ARD: ARD soil; -ARD: gamma-irradiated ARD soil; and Control: soil with no apple history). We investigated the microbial community composition by 16S rRNA gene amplicon sequencing (bacteria and archaea) along the soil–root continuum (bulk soil, rhizosphere and rhizoplane). Significant differences in microbial community composition and structure were found between +ARD and -ARD or +ARD and Control along the soil–root continuum, even for plants exposed simultaneously to two different substrates (-ARD/+ARD and Control/+ARD). The substrates in the respective split-root compartment defined the assembly of root-associated microbial communities, being hardly influenced by the type of substrate in the respective neighbor compartment. Root-associated representatives from Actinobacteria were the most dynamic taxa in response to the treatments, suggesting a pivotal role in ARD. Altogether, we evidenced an altered state of the microbial community in the +ARD soil, displaying altered alpha- and beta-diversity, which in turn will also impact the normal development of apple rhizosphere and rhizoplane microbiota (dysbiosis), concurring with symptom appearance. Abstract : Microbial determinants of ARD.